A Multilevel Investigation of the Motivational Mechanisms Underlying Knowledge Sharing and Performance - Quigley, Narda R.; Tesluk, Paul E.; Locke, Edwin A.; Bartol, Kathryn M. (Organization Science, 2007)
This study draws on three different, yet complementary, theories of motivation, which we combine in an interactive manner, to explain the mechanisms that underlie the exchange between knowledge providers and recipients and ultimately impact performance. More specifically, we use incentive, goal-setting-social cognitive, and social motivation theories to examine knowledge sharing within dyads and its influence on individual performance. One hundred and twenty participants functioning as interdependent manager dyads completed a strategic decision-making simulation. Hierarchical regression and random coefficient modeling techniques were used to test hypothesized relationships. Results demonstrated that the effect of group-oriented incentive systems on the knowledge provider was enhanced when more positive norms for knowledge sharing existed among dyad members. The recipient’s self-efficacy had a stronger relationship with performance goals when the recipient trusted the provider. Finally, self-set goals and knowledge sharing had both direct and interactive effects on individual performance. We argue that these findings constitute a useful advance in middle-range motivation (Landy and Becker 1987, Pinder 1984) theory pertaining to knowledge sharing and utilization.